Moderate Exercise Training Combined With a High-Fat and Sucrose Diet Protects Pancreatic Islet Function in Male C57BL/6J Mice - Veras, Katherine; Lucena, Camila Ferraz; Goedcke, Julia; Evangelista, Fabiana S.; Carpinelli, Angelo; Carvalho, Carla Roberta de Oliveira (Frontiers in Endocrinology, 2022)
Obesity is mainly caused by excess energy intake and physical inactivity, and the number of overweight/obese individuals has been steadily increasing for decades. Moreover, previous studies showed that rodents fed westernized diets exhibit endocrine pancreas deterioration and a range of metabolic disorders. This study evaluated the effects of exercise training on pancreatic islet cell viability and function in male C57BL/6J mice consuming a high-fat and sucrose diet. The mice were divided into four groups: HFDS-high-fat and sucrose diet: 20% carbohydrate, 20% protein, 60% fat and 20% sucrose; C-control diet: 70% carbohydrate, 20% protein, and 10% fat; HFDSTR-high-fat and sucrose diet and treadmill running at 60% peak treadmill velocity for 30 minutes, 5d/week and CTR-control diet and treadmill running. After eight weeks, the HFDS mice displayed increased body (P<0.001) and epididymal, inguinal and retroperitoneal adipose tissue mass (P<0.01) and exhibited insulin resistance (P<0.01), glucose intolerance (P<0.001), impaired glucose-stimulated insulin secretion (GSIS) and no response in the cytosolic ROS content. The HFDS group's pancreatic islet cells were 31% less viable, and 59% more were apoptotic than the C group (P<0.05). All of these alterations, except for adipose tissue weight, were attenuated by training (P<0.05), with some parameters reverting to C group levels. Furthermore, HFDSTR mice had 63% more viable cells and 20% fewer apoptotic cells than the HFDS group (P<0.01). Our results demonstrated that eight weeks of exercise training could protect the pancreatic islets against the deleterious effects of the high-fat and sucrose diet, improving insulin sensitivity, pancreatic viability and GSIS. Thus, exercise training may slow down and/or prevent adverse metabolic effects associated with consuming a westernized diet. Additional human studies are necessary to test this hypothesis.